Cybersecurity and Digital Skills Development: a Proposal for Digital Literacy at Early Ages - Bustillos Ortega, Olda (2023)
Children are the most vulnerable segment of this cyberphysical society and can be easily exploited due to their level of perception of cyber risk. Starting education and the development of digital skills at an early age encourages this population topursue professional careers such as cybersecurity in the future and contribute in a sustainable way to closing the gap in the workforce. Using a qualitative approach, a documentary review, a literature review, and consultation with academic experts are carried out to propose a digital literacy program at an early age. As a case study, the Digital Literacy Program of the International University of the Americas of Costa Rica and the experiences with the Cybersecurity Workshop for Children are presented. Workshop aimed at the development of digital skills, cyber well-being at an early age and children’s interest in following new professional careers. It aims to reduce the gap in the workforce in cybersecurity positions with training programs at an early age, raising awareness about cybersecurity risks, their evolution, their impact on society and highlighting their importance in a world increasingly driven by technology.